Multi-Element Bioimaging of Arabidopsis thaliana Roots . Issue 2 (26th August 2016) - Persson, Daniel Pergament; Chen, Anle; Aarts, Mark G.M.; Salt, David E.; Schjoerring, Jan K.; Husted, Søren
Abstract : Multielement imaging of ion transport and distribution in Arabidopsis roots shows distinct spatial and dynamic gradients. Abstract: Better understanding of root function is central for the development of plants with more efficient nutrient uptake and translocation. We here present a method for multielement bioimaging at the cellular level in roots of the genetic model system Arabidopsis (Arabidopsis thaliana). Using conventional protocols for microscopy, we observed that diffusible ions such as potassium and sodium were lost during sample dehydration. Thus, we developed a protocol that preserves ions in their native, cellular environment. Briefly, fresh roots are encapsulated in paraffin, cryo-sectioned, and freeze dried. Samples are finally analyzed by laser ablation-inductively coupled plasma-mass spectrometry, utilizing a specially designed internal standard procedure. The method can be further developed to maintain the native composition of proteins, enzymes, RNA, and DNA, making it attractive in combination with other omics techniques. To demonstrate the potential of the method, we analyzed a mutant of Arabidopsis unable to synthesize the metal chelator nicotianamine. The mutant accumulated substantially more zinc and manganese than the wild type in the tissues surrounding the vascular cylinder. For iron, the images looked completely different, with iron bound mainly in the epidermis of the wild-type plants but confined to the cortical cell walls of the mutant. The method offers the power of inductively coupled plasma-mass spectrometry to be fully employed, thereby providing a basis for detailed studies of ion transport in roots. Being applicable to Arabidopsis, the molecular and genetic approaches available in this system can now be fully exploited in order to gain a better mechanistic understanding of these processes.